2019
DOI: 10.2147/idr.s200988
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative study of antimicrobial resistance and biofilm formation among Gram-positive uropathogens isolated from community-acquired urinary tract infections and catheter-associated urinary tract infections</p>

Abstract: Background: Gram-positive cocci have emerged to be an important cause of urinary tract infection (UTI) both in community-acquired UTI (Com-UTI) and catheter-associated urinary tract infection (CA-UTI). The objective of this study was to investigate the frequency of Gram-positive cocci urinary tract infections, their susceptibility patterns to commonly used antimicrobial agents and the biofilm forming property with respect to catheter-associated UTI and community-acquired UTI. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 38 publications
1
33
0
3
Order By: Relevance
“…To the best of our knowledge, this is the longest-spanning study reporting on the prevalence and susceptibility of this group of uropathogens in Hungary. In contrast to previous studies, dating back some 20–30 years (where the reported prevalence of Enterococcus spp., S. aureus and S. saprophyticus was 2–20%, 0.2–6% and 0.5–8%, respectively), based on current literature results, their prevalence is around 8–35%, 0.5–13% and 5–20%, respectively 48 – 55 . This increase is prevalence is especially notable in patients affected by recurrent UTIs (recurrence 3 or more times in 6 months) 44 .…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…To the best of our knowledge, this is the longest-spanning study reporting on the prevalence and susceptibility of this group of uropathogens in Hungary. In contrast to previous studies, dating back some 20–30 years (where the reported prevalence of Enterococcus spp., S. aureus and S. saprophyticus was 2–20%, 0.2–6% and 0.5–8%, respectively), based on current literature results, their prevalence is around 8–35%, 0.5–13% and 5–20%, respectively 48 – 55 . This increase is prevalence is especially notable in patients affected by recurrent UTIs (recurrence 3 or more times in 6 months) 44 .…”
Section: Discussionmentioning
confidence: 83%
“…Although the susceptibility-reporting for some of the antibiotics (e.g., fusidic acid, rifampicin, erythromycin, clindamycin, doxycycline and tigecycline) might seem frivolous in the context of the therapy of UTIs (as these drugs are not used in the therapy of these infections), the reporting of these results for epidemiological purposes is of interest, especially because not many studies are available regarding GPCs as uropathogens from Europe 66 . The prevalence of MRSA/VRSA and VRE isolates from urinary samples was advantageous in our study, and the levels of these isolates were similarly low in other literature reports as well, especially if we compare resistance levels of urinary isolates with invasive isolates (vancomycin-resistant E. faecalis : 0.0% [2008], 0.4% [2017]; vancomycin-resistant E. faecium : 2.8% [2008], 28.3% [2017]; MRSA: 22.5% [2008], 23.6% [2017], data from the European Antimicrobial Resistance Surveillance Network [EARS-Net]) 48 56 , 67 , 68 . On the other hand, the resistance levels to auxillary antimicrobials (aminoglycosides, fluoroquinolones) was shown to be high, and presenting in an increasing tendency (HLAR in enterococci: 53.3% [2008], 62.0% [2017], data from EARS-Net) 48 56 , 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasal carriers of S. aureus might develop an endogenous infection, and consequently, they pose a threat of transmitting infection to susceptible individuals [ 1 ] . Accordingly, S. aureus accounts for the high numbers of nosocomial and community-acquired infections, as well as biomaterial contamination [ 2 , 3 ] . Moreover, these microorganisms have the potential to colonize medical catheters, tubing, surgical drains, and central lines by forming biofilms, which render them resistant to host defense mechanisms and antimicrobial therapy [ 4 , 5 ] .…”
Section: Introductionmentioning
confidence: 99%